2022
DOI: 10.23887/jp2.v5i3.51494
|View full text |Cite
|
Sign up to set email alerts
|

Museum Virtual Tour Development Using 3D Vista as a History Learning Source

Abstract: Visits to museums are also a means of learning that arouses curiosity and provides a different nuance in learning. The problem today is that distance and time are not possible if the teacher brings students to the location of the museum. An alternative solution to these problems is to use technology. This study aims to develop a virtual tour learning tool at the Sriwijaya museum by using the 3D Vista application as a source for learning history. The stages of this research adapt to the product development rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…Permasalahan yang dialami pengelola Museum Situs Semedo dari sektor pemasaran atau promosi yaitu pengunjung lokal yang hanya berasal dari Kabupaten Tegal saja. Padahal adanya museum ini dapat dimanfaatkan sebagai edukasi sejarah untuk masyarakat dengan cakupan wilayah yang lebih luas lagi (Syukur et al, 2022) (Anita et al, 2021). Semakin banyaknya jumlah pengunjung dan perluasan asal wilayah pengunjung, diharapkan nantinya dapat menambah pendapatan Museum Semedo jika harga tiket sudah dikomersialisasikan sehingga perawatan dan pengembangan museum dapat dilakukan optimal dengan tambahan dana yang berasal dari tiket masuk.…”
Section: A Latar Belakangunclassified
“…Permasalahan yang dialami pengelola Museum Situs Semedo dari sektor pemasaran atau promosi yaitu pengunjung lokal yang hanya berasal dari Kabupaten Tegal saja. Padahal adanya museum ini dapat dimanfaatkan sebagai edukasi sejarah untuk masyarakat dengan cakupan wilayah yang lebih luas lagi (Syukur et al, 2022) (Anita et al, 2021). Semakin banyaknya jumlah pengunjung dan perluasan asal wilayah pengunjung, diharapkan nantinya dapat menambah pendapatan Museum Semedo jika harga tiket sudah dikomersialisasikan sehingga perawatan dan pengembangan museum dapat dilakukan optimal dengan tambahan dana yang berasal dari tiket masuk.…”
Section: A Latar Belakangunclassified
“…As users engage solely through screens, mice, and keyboards, they struggle to discern real-world pathways and obstacles, easily succumbing to distractions from other interfaces, thus disrupting their viewing experience at any given moment. To surmount these constraints and enrich user immersion and engagement, researchers and developers have explored diverse technologies and methodologies, including recommendation systems [39,40], personalized navigation [41][42][43], virtual assistants [44][45][46], and navigation devices [47].…”
Section: Virtual Museum Navigation Experiencementioning
confidence: 99%
“…VT also functions as a tool for comprehensively exploring tourist attractions and can help determine whether a visit in person is worthwhile (El-Said & Aziz, 2022). Generally, virtual tours provide the illusion to viewers that they have virtually visited a location merely by observing it on a screen (Gutowski & Klos-Adamkiewicz, 2020) (Syukur, Dewie, & Oktarina, 2022). Past research has shown a positive reception of virtual tours by the public (Anita, Wijaya, Sarastiani, Kusumo, & Santi, 2021).…”
Section: Introductionmentioning
confidence: 99%